On the Frequencies for Structural Health Monitoring in Plates with Symmetrical Damage: An Analytical Approach - Lopes, Kayc W. [UNESP]; Gonsalez-Bueno, Camila G. [UNESP]; Bueno, Douglas D. [UNESP] (Springer Nature, 2022)
The damage detection process in structures has been an important challenge for the engineering community. The design of structural health monitoring (SHM) systems usually involves selection of actuators and sensors, their positions on the structure and post-processing of output signals. This article presents an approach to determine the optimal frequencies for damage detection in plates considering the perpendicular incidence of longitudinal waves into the damage. At these optimal frequencies are observed the maximum reflected and the minimum transmitted longitudinal wave amplitudes, which are recommended to achieve the damage detection due to their higher differences in wave amplitudes when comparing healthy and damaged conditions. Higher values of two damage detection indexes are obtained at the optimal frequencies. Experimental tests are carried out considering a rectangular aluminum plate with circular piezoelectric transducers. The experimental results demonstrate the proposed approach, and highlight the importance of defining optimal frequencies to detect damage in plates.
Keywords: Frequencies for Perpendicular Incidence; Longitudinal Waves; Plates; Symmetrical Damage